Dampak kesenjangan literasi keuangan dan locus of control terhadap perilaku konsumtif pengguna paylater - Afrita Miranda; Ita Nuryana (Universitas Negeri Surabaya, 2026)
Rapid digitization and the growth of PayLater services have raised concerns about an increase in consumptive and impulsive purchasing behavior, especially among users with low financial literacy and external locus of control. This study aims to integrate financial literacy and locus of control as key variables that influence the consumptive behavior of PayLater users. It analyzes the impact of financial literacy gaps and locus of control on the relationship between financial literacy and consumptive behavior. This study uses a systematic literature review method from 15 articles published between 2020 and 2025. The results of this study found that financial literacy is essential in reducing consumptive behavior. However, external locus of control can still encourage impulsive buying, even in individuals with good financial literacy, and PayLater itself has the potential to increase impulsive spending.